Plant-Mediated Horizontal Transmission of Asaia Between White-Backed Planthoppers, Sogatella furcifera - Li, Fei; Hua, Hongxia; Han, Yongqiang; Hou, Maolin (Frontiers in Microbiology, 2020)
Asaia is a bacterial symbiont of sugar-feeding insects that has been shown to be vertically transmitted by maternal transmission and paternal transmission mechanism, and to be horizontally transmitted via co-feeding artificial diet and venereal routes. Here, the first case of plant-mediated horizontal transmission of Asaia between white-backed planthoppers (WBPH), Sogatella furcifera, was reported. In Asaia-infected WBPH, Asaia was detected mostly in salivary glands and to a less extent in stylets. After fed by the Asaia-infected WBPH at 12 h post infestation, the rice leaf sheaths were all positive with Asaia, where Asaia persisted for at least 30 d but was localized in the feeding sites only. When confined to Asaia-infected leaf sheaths for 7 d at the sites pre-infested by the Asaia-infected WBPH, all Asaia-free WBPH became infected with Asaia and the acquired Asaia could be vertically transmitted to their offspring. Phylogenetic analysis confirmed an identical Asaia strain in the Asaia-infected donor WBPH, the Asaia-infected leaf sheaths, and the newly infected recipient WBPH. Our findings provide direct evidence for the first time that rice plant can mediate horizontal transmission of Asaia between WBPH, which may contribute to the spread of Asaia in the field WBPH populations.